2019
DOI: 10.1016/j.hpb.2019.10.1039
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of tumor markers and their impact on prognosis in gallbladder, bile duct, and cholangiocellular carcinomas – A pilot study

Abstract: Background: The aim was to construct a risk score model to predict IGBC, developed through statistical modelling, based on our groups previous findings. Methods: Data from cholecystectomies registered in the Nationwide Swedish Register for Gallstone Surgery were analysed. The derivation cohort underwent surgery 2007-2014 and the validation cohort 2015-2016. From the multivariable logistic regression in the derivation cohort, an additive risk model, based on the odds ratio, was constructed and validated. The sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Our study highlights that preoperative NLR and LMR values were independent predictors of OS in patients with DBDC who underwent pancreaticoduodenectomy. Several studies have reported that preoperative indicators, such as serum albumin and CRP levels, as well as widely recognized tumor markers (CEA and CA 19-9) may also serve as prognostic indicators of biliary tract cancer outcomes [10][11][12][13][14]; however, the NLR and LMR scored over these factors in this study. The prognostic value of these inflammatory biomarkers has been demonstrated in biliary tract cancer [15,16].…”
Section: Discussioncontrasting
confidence: 54%
“…Our study highlights that preoperative NLR and LMR values were independent predictors of OS in patients with DBDC who underwent pancreaticoduodenectomy. Several studies have reported that preoperative indicators, such as serum albumin and CRP levels, as well as widely recognized tumor markers (CEA and CA 19-9) may also serve as prognostic indicators of biliary tract cancer outcomes [10][11][12][13][14]; however, the NLR and LMR scored over these factors in this study. The prognostic value of these inflammatory biomarkers has been demonstrated in biliary tract cancer [15,16].…”
Section: Discussioncontrasting
confidence: 54%
“…In incidental gallbladder cancer, tumour markers are usually not available from the preoperative assessment, and thus the prognostic role of frequently used tumour markers such as carbohydrate antigen (CA) 19‐9 or carcinoembryonic antigen (CEA) is not known. For gallbladder cancer in general, a high preoperative CA 19‐9 or CEA value is considered a poor prognostic sign, as it relates to tumour burden. In general, the prognostic accuracy of both CEA and CA 19‐9 is rather low and non‐specific for raised values, and the best information may be having a value within the normal range, which is usually associated with a good prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…For gallbladder cancer in general, a high preoperative CA 19‐9 or CEA value is considered a poor prognostic sign, as it relates to tumour burden. In general, the prognostic accuracy of both CEA and CA 19‐9 is rather low and non‐specific for raised values, and the best information may be having a value within the normal range, which is usually associated with a good prognosis. Other tumour markers, such as CA 242 and thymidine kinase, have been proposed as promising or better than CEA and CA 19‐9, but are non‐specific and require further validation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of CEA as well as CA 19-9 levels on survival in BTC is contradictive. 19,[21][22][23] One reason for the inconclusive results may be the different cutoff values that were used in the respective studies. In our study, we used the ULN as cutoff values.…”
Section: Discussionmentioning
confidence: 99%